(3GdhVY Ydi GdLgGJ aj GdHSGFW hGdefMQaGJs - (3Ydj GdeGdcj GdCfOdSjs; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjfs
(3ChdgG (B:s
(3bO GSJNQJ Gddg SHMGfg hJYGdi ai JdNjV gPg GdQSGdg s
(3BNQgG (B:s
(3ZjQ cGed GYde Gf GdbhS GdcHQi YHGQg Yf GdLOhd GdBjef ai cd fMQGa s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B485 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B110 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B205) s
Keywords: (3Gdadcs